The philosophy of software : code and mediation in the digital age - Berry, David M. (Basingstoke : Palgrave Macmillan, 2011)
This work is a critical introduction to code and software that develops an understanding of its social and philosophical implications in the digital age. Written specifically for people interested in the subject from a non-technical background, the book provides a lively and interesting analysis of these new media forms.
boek